Job polarization, task prices and the distribution of task returns - Chiara Cavaglia; Ben Etheridge (University of Essex, Institute for Social and Economic Research (ISER), 2017)
We make two contributions to understanding the large shifts in occupational structure seen across developed countries. First, we estimate underlying prices on occupations, grouped by predominant task, using panel data from the UK and Germany. In both countries, price growth is positively associated with employment share growth. This pattern, which disappears with observed wages, is consistent with changes to labour demand, such as from technological changes. Second, we use the underlying Roy framework to further interpret these movements, by identifying the covariance structure of returns across tasks. The estimates show the importance of sorting based on productivity in abstract tasks.
Keywords: J20; J24; J31; 330; job polarization; occupational choice; Roy model